2005
DOI: 10.1073/pnas.0408986102
|View full text |Cite
|
Sign up to set email alerts
|

Homology-dependent methylation in primate repetitive DNA

Abstract: In mammals, several studies have suggested that levels of methylation are higher in repetitive DNA than in nonrepetitive DNA, possibly reflecting a genome-wide defense mechanism against deleterious effects associated with transposable elements (TEs). To analyze the determinants of methylation patterns in primate repetitive DNA, we took advantage of the fact that the methylation rate in the germ line is reflected by the transition rate at CpG sites. We assessed the variability of CpG substitution rates in nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…26 Furthermore, Meunier et al also recently reported that the methylation pattern in primate repetitive DNA is homology-dependent. 27 Therefore, it is likely that 2 nonhomologous alleles resulting from nucleotide polymorphism affect promoter methylation of the p14 ARF gene by causing heterozygous methylation within a repeat sequence.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, Meunier et al also recently reported that the methylation pattern in primate repetitive DNA is homology-dependent. 27 Therefore, it is likely that 2 nonhomologous alleles resulting from nucleotide polymorphism affect promoter methylation of the p14 ARF gene by causing heterozygous methylation within a repeat sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the substitution rate at CpG dinucleotides may be negatively correlated with GC content (defined as the percentage of G and C nucleotides). There are conflicting conclusions on this relationship [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We used a parsimony method [19][20][21][22][23] to identify sites that have been part of a CpG dinucleotide in the recent past (''CpG sites''). In addition, using the same method, we identified sites that have been part of a GpC dinucleotide (''GpC sites'', see the Methods section for details).…”
Section: Cpg Substitution Rate Exhibits Substantial Regional Variationmentioning
confidence: 99%
“…This pattern of differential methylation was also detected between homologous ancestral blocks and may reflect a buffer of gene dosage resulting from formation of the amphidiploid (Paun et al 2010). In primate genomes, the degree of CpG methylation in homologous genomic regions varies between human, chimpanzee and baboon (Meunier et al 2005), suggesting the existence of a homology-dependent methylation (HDM) mechanism.…”
Section: Discussionmentioning
confidence: 95%